1985
DOI: 10.1128/iai.49.1.219-224.1985
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bacterial competition on the opsonization, phagocytosis, and intracellular killing of microorganisms by granulocytes

Abstract: The ingestion of Escherichia coli by human granulocytes in vitro was reduced in the presence of Bacteroides fragilis or Staphylococcus aureus. This reduction of ingestion proved to be mainly attributable to the absence of opsonization of E. coli, which was due to complement consumption by B. fragiis and S. aureus. The intracellular killing of E. coli was decreased in the presence of B. fragiis and S. aureus because of consumption of complement components required for extracellular stimulation of granulocytes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Bacteroides species are frequently isolated in large numbers from chronic purulent lesions as part of a mixed microbial flora (9,40). Their ability to induce abscess formation as part of a mixed infection appears to be due to their local effects on the functions of polymorphonuclear leukocytes (PMN) (6,17,18,30,39,41). The enteric pathogen Bacteroides fragilis appears to affect PMN microbicidal activity through production and release of short-chain fatty acids (39,41), whereas the periodontal pathogen Porphyromonas (formerly Bacteroides) gingivalis (47) inhibits PMN functions by cell-associated molecules and by constituents of culture supernatants (25,30,46,54,58).…”
mentioning
confidence: 99%
“…Bacteroides species are frequently isolated in large numbers from chronic purulent lesions as part of a mixed microbial flora (9,40). Their ability to induce abscess formation as part of a mixed infection appears to be due to their local effects on the functions of polymorphonuclear leukocytes (PMN) (6,17,18,30,39,41). The enteric pathogen Bacteroides fragilis appears to affect PMN microbicidal activity through production and release of short-chain fatty acids (39,41), whereas the periodontal pathogen Porphyromonas (formerly Bacteroides) gingivalis (47) inhibits PMN functions by cell-associated molecules and by constituents of culture supernatants (25,30,46,54,58).…”
mentioning
confidence: 99%
“…Although the sole use of S. aureus was sufficient to accomplish proof-of-principle, additional studies should be performed to confirm this spectrum in neutrophils for phagocytosis of other bacteria. An early study of Dijkmans et al, showed altered phagocytosis of Escherichia coli by neutrophils when simultaneously exposed to S. aureus ( 32 ). They mainly attributed this to competitive opsonization, but multiple mechanisms or intrinsic differences may have played a role.…”
Section: Discussionmentioning
confidence: 99%
“…A number of investigators have provided evidence that Bacteroides sp. activates the complement system in vitro via the classical and alternative pathways (for a review see reference 2), and Dijkmans et al (4) recently showed that B. fragilis may cause complement consumption in vitro that in turn decreases phagocytosis of E. coli by polymorphonuclear leukocytes. However, with intraperitoneal injections of mixed cultures in mice (17) or rats (5), other authors failed to demonstrate any apparent effect of B. fragilis on the clearance of E. coli from the peritoneal cavity of experimental animals and concluded that the above mechanisms are not operative in vivo.…”
Section: Discussionmentioning
confidence: 99%